2006
DOI: 10.1088/0022-3727/39/24/007
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence studies of CaS : Bi nanocrystalline phosphors

Abstract: The thermoluminescence (TL) studies of CaS : Bi nanocrystalline phosphors prepared by the wet chemical co-precipitation method and exposed to γ-rays have been discussed. The average grain size of the samples was estimated as 35 nm using Scherrer's equation. The samples exhibit a complex TL glow curve with multiple peaks. Sample exposed to γ-rays showed that the TL intensity increases linearly as the radiation doses increased in the 1.012–40.48 mGy range. The trap parameters namely, activation energy (E), order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…It is known that TL response of any material is different for different ionizing radiations or ions [10][11], so it is important to know about the nature of these centres or traps. Therefore, in continuation to our previous work, this report aims at the systematic thermoluminescence study of the cerium doped SrS nanostructures exposed to Co-60 gamma rays at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that TL response of any material is different for different ionizing radiations or ions [10][11], so it is important to know about the nature of these centres or traps. Therefore, in continuation to our previous work, this report aims at the systematic thermoluminescence study of the cerium doped SrS nanostructures exposed to Co-60 gamma rays at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Being a wide bandgap (4.43 eV) [7] semiconductor, it is investigated with wide range of dopants such as Sm 3+ , Ce 3+ , Eu 2+ , Bi 3+ , etc. [11][12][13][14]. These days nanotechnology has stimulated interest in the properties of nano form of the matter.…”
Section: Introductionmentioning
confidence: 99%
“…sensors, optical memory devices, scintillators and radiation dosimetry [2,[10][11][12][13]. Kumar et al [8,14] have investigated the thermoluminescence properties of CaS:Bi nanophosphors exposed to UV and gamma radiations. Kojima et al [15] have recently reported the effect of strontium and lithium ions on afterglow time of red emitting CaS:Eu, Pr phosphor upon visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%